Comparison of the surface microhardness of heat curing and self-curing acrylic resin discs in different time periods - Carbajal Córdova, Sarahí Paola (2021)
Objective: To compare surface microhardness of self-curing and heat-curing acrylic discs in different periods of time. Methodology: This in vitro laboratory study, consisted of 80 acrylic discs (Vitalloy), 40 self-cured (A) and 40 heat-cured (T) divided into 8 subgroups: self-cure control group GA0 (n=10), heat-cure control group GT0 (n=10), self-cure group stored 1 day GA1 (n=10), heat-cure group stored 1 day GT1 (n=10), self-cure group stored 7 days GA7 (n=10), heat-cure group stored 7 days GT7 (n=10), self-cure group stored 21 days GA21 (n=10), and heat-cure group stored 21 days GT21 (n=10). Vickers surface microhardness of the acrylic resin discs previously stored in physiological serum was then evaluated at the different time periods. Subsequently, the data was statistically analyzed using ANOVA and TUKEY tests. The level of statistical significance was set at P <0.05. Results: The values found were in GT0 (20.45±0.93 Vickers hardness number [VHN]); GA0 (16.25±0.79 VHN); GT1 (20.08±0.66 VHN); GA1 (15.97±0.78 VHN); GT7 (19.57±1.54 VHN); GA7 (14.33±0.48 VHN); GT21 (19.17±1.26 VHN); GA21 (14.64±0.52 VHN), with statistically significant differences between the self-cure and heat-cure groups (P<0.001). Conclusion: The groups of heat-curing acrylic resins presented better microhardness values than the groups of self-curing acrylic resins in the different time periods evaluated.